(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
This work presents a tax planning model account applicable to the management of companies not formed as legal persons according to Argentine corporate and tax legislation. For its development, the modeling methodology was used, which aims to quantitatively estimate and predict the behavior of certain variables to identify possible scenarios and make decisions. It is a tool for the analysis and processing of patrimonial, economic and financial data that allows the generation of useful information for professional advice by accountants and for business decision[1]making, particularly those related to tax strategy, planning and management. Starting from hypothetical initial values, the function of the model becomes four possible scenarios: a) allocate the entire result of the period to finance the level of consumption (that is, without investing); b) invest half of the result of the period; c) invest half of the result of the period without sacrificing the level of consumption and without resorting to debt; d) invest half of the result of the period without sacrificing the level of consumption and investment and under the impossibility of generating additional own income. Under these premises, the investment must be financed with debt, which will imply deciding whether or not to resort to said source of financing.